2018
DOI: 10.1103/physrevb.98.104420
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetocaloric effect in an exchange-frustrated GdCrTiO5 antiferromagnet

Abstract: We report the effect of exchange frustration on the magnetocaloric properties of GdCrTiO5 compound. Due to the highly exchange-frustrated nature of magnetic interaction, in GdCrTiO5, the long-range antiferromagnetic ordering occurs at much lower temperature TN =0.9 K and the magnetic cooling power enhances dramatically relative to that observed in several geometrically frustrated systems. Below 5 K, isothermal magnetic entropy change (-∆Sm) is found to be 36 J kg −1 K −1 , for a field change (∆H) of 7 T. Furth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 67 publications
3
13
0
Order By: Relevance
“…3(b), we have fitted the inverse susceptibility in the paramagnetic region. The x-axis intercept represents the Curie-Weiss temperature (θ CW ) ∼ −18 K. The calculated frustration parameter f =−θ N /T N ∼5.3 is moderate compared to the strongly geometrically frustrated magnets (f >10) [26,27]. From the fitting parameters, the effective mag- netic moment (µ ef f ) is found to be 9.7 µ B per formula unit, which is close to the theoretical value (9.72 µ B ) expected for Tb 3+ ion.…”
Section: Resultsmentioning
confidence: 95%
“…3(b), we have fitted the inverse susceptibility in the paramagnetic region. The x-axis intercept represents the Curie-Weiss temperature (θ CW ) ∼ −18 K. The calculated frustration parameter f =−θ N /T N ∼5.3 is moderate compared to the strongly geometrically frustrated magnets (f >10) [26,27]. From the fitting parameters, the effective mag- netic moment (µ ef f ) is found to be 9.7 µ B per formula unit, which is close to the theoretical value (9.72 µ B ) expected for Tb 3+ ion.…”
Section: Resultsmentioning
confidence: 95%
“…We also observed that the frustration factor, defined as f frus = |Θ Weiss |/ T C , yields f frus = 0.65, 0.78, and 0.75, respectively. Theses values are less than 1 and indicate that the system is not geometrically frustrated. The observed paramagnetic moments ( p eff ) are 11.1, 10.4, and 10.2 μ B /f.u. for the three fields mentioned (50 Oe, 500 Oe, and 5 kOe).…”
Section: Resultsmentioning
confidence: 97%
“…A few contain precious Rh (e.g., FeRh [24,222,278,279] and Tb 3 Rh [270]). Many contain critical rare earth, such as Eu in Eu 2 In [140], EuTiO 3 [114,135,156,195] doped with Al [113], Cr [196], Mn [134], Co [151], Ni [119], Ba [157,206], Nb [110,170,195] and Eu in other compounds [133,232,240,251]; Gd in GdAlO 3 [158], GdFeO 3 [138,162], GdCrO 3 [183], GdCrO 4 -ErCrO 4 [202], GdScO 3 [117,124], Gd 2 CoMnO 6 [155], Gd 2 BaNiO 5 [152], GdCrTiO 5 [143], GdCo 2 B 2 [271], GdCoC 2 [171], RuSr 2 GdCu 2 O 8 [208], etc. ; Tb in TbFeO 3 [176], TbMn 2 O 5 [179], Tb 2 CoMnO 6 [132], Tb 5 Ge 2−x Si 2−x Mn 2x [255], Tb 4 Gd 1 Si 2.035 Ge 1.935 Mn 0.03 [197], etc.…”
Section: ∆S T T C (K) ∆T S (K)mentioning
confidence: 99%